2021
DOI: 10.1137/20m1364953
|View full text |Cite
|
Sign up to set email alerts
|

Global Well-posedness for the Focusing Cubic NLS on the Product Space $\mathbb{R} \times \mathbb{T}^3$

Abstract: In this paper, we prove the global well-posedness for the focusing, cubic nonlinear Schrödinger equation on the product space R × T 3 with initial data below the threshold that arises from the the ground state in the Euclidean setting. The defocusing analogue was discussed and proved in Ionescu-Pausader [22] (Comm. Math. Phys. 312 (2012), no. 3, 781-831).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Threshold assumptions are necessary and new ingredients are needed to handle this type of problems. See [37] for a global well-posedness result and [7,28] for two very recent scattering result. Moreover, see [14,24,27] for the Euclidean result.…”
Section: ḣ1mentioning
confidence: 99%
See 1 more Smart Citation
“…Threshold assumptions are necessary and new ingredients are needed to handle this type of problems. See [37] for a global well-posedness result and [7,28] for two very recent scattering result. Moreover, see [14,24,27] for the Euclidean result.…”
Section: ḣ1mentioning
confidence: 99%
“…We refer to [8,13,25] for some important Euclidean results. Moreover, we refer to [6,5,18,20,21,22,23,26,33,34,37,39,40,41] with regard to the tori case and the waveguide case. We may roughly think of the waveguide case as the "intermediate point" between the Euclidean case and the tori case since the waveguide manifold is the product of the Euclidean space and the tori.…”
mentioning
confidence: 99%
“…and scattering of the defocusing nonlinear Schrödinger equations on the cylinder R 2 × T (See [9,10,51]), there are very few result on the long time behavior of the solutions of the focusing nonlinear Schrödinger equations on the cylinders. We refer to [49] for a result on the orbital stability in the focusing case, and global well-posedness result in [56].…”
Section: Introductionmentioning
confidence: 99%
“…Following the nowadays well-known concentration compactness arguments initiated by Kenig and Merle [35] and the so-called Black-Box-Theory, Ionescu, Pausader and Staffilani [30,31,32] showed that defocusing energy-critical NLS on T 3 , R × T 3 and on the hyperbolic space H 3 are always globally well-posed. By appealing to suitable variational arguments, Yu, Yue and Zhao [51,50] utilized the Black-Box-Theory to prove that solutions of the focusing energy-critical NLS on T 4 and R × T 3 lying below ground states are always globally well-posed.…”
Section: Introductionmentioning
confidence: 99%